PENGARUH CITRA MEREK, KONTEN, DAN e-SERVICE QUALITY TERHADAP KEPUASAN PELANGGAN SPOTIFY ( STUDI KASUS MAHASISWA PROGRAM STUDI MANAJEMEN ANGKATAN 2022 – 2023 UNIVERSITAS METHODIST INDONESIA - Tri Hartati Margaretha Sihombing; Anton A.P. Sinaga; Junika Napitupulu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid development of digital technology has significantly changed consumer behavior in accessing entertainment services, particularly music streaming platforms such as Spotify. Intensifying competition in the industry requires companies to better understand the factors that influence customer satisfaction. This study aims to analyze the effect of brand image, content, and e-service quality on customer satisfaction among students of the Management Study Program, class of 2022–2023, at the Indonesian Methodist University.This research adopts a quantitative approach using a survey method. Data were collected through questionnaires distributed to 227 respondents who are active Spotify users, selected using a purposive sampling technique. The data were analyzed using multiple linear regression with the assistance of IBM SPSS software.The findings indicate that brand image, content, and e-service quality each have a positive and significant effect on customer satisfaction. Furthermore, when tested simultaneously, these three variables also show a positive and significant influence on Spotify customer satisfaction. The coefficient of determination reveals that brand image, content, and e-service quality collectively explain a substantial proportion of the variance in customer satisfaction, while the remaining variance is attributed to other factors beyond the scope of this study.These results highlight the importance of maintaining a strong brand image, providing relevant and high-quality content, and continuously improving e-service quality to enhance customer satisfaction. This is particularly important for students, who represent a key segment of active users of digital streaming services.